Analisis Fungsi Keuntungan Usahatani Kentang di Kecamatan Kayu Aro Barat Kabupaten Kerinci: Penelitian - Nainggolan, Maria Rosalinda; Nainggolan, Saidin; Yulismi, Yulismi (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to analyze the profit function of potato farming in Kayu Aro Barat District, Kerinci Regency. Specifically, the study describes the characteristics of potato farming, calculates the profit obtained by farmers, and identifies the factors influencing profit levels. Data were collected through surveys using a simple random sampling method involving 62 potato farmers in the study area. The analysis employed includes cost and revenue analysis, income and profit calculation, as well as the estimation of the Cobb-Douglas profit function. The results show that potato farming production costs are dominated by seed, fertilizer, and labor expenses. The average revenue earned by farmers exceeds the total production cost, indicating that potato farming is profitable. Regression analysis reveals that seed prices, fertilizer prices, labor wages, and land rent costs significantly affect profit levels. The value of return to scale is in the condition of increasing return to scale (>1), indicating that the use of production inputs is not yet optimal and that profit can still be increased if inputs are managed more efficiently. Therefore, optimizing input allocation is necessary to maximize the profitability of potato farming in Kayu Aro Barat District.